PENGEMBANGAN SISTEM PRESENSI DAN MONITORING PEGAWAI DI DINAS PERUMAHAN DAN KAWASAN PERMUKIMAN KOTA SALATIGA - Oggy Dwi Ziduhu Zebua; Rudy Latuperissa (STMIK Subang, 2026)
This research is motivated by the continued use of manual attendance recording, which often leads to data inaccuracies, delayed reporting, and inefficient data management. The study focuses on how to design and develop a digital attendance system capable of accurately recording employee presence, displaying check-in and check-out times, and automatically generating attendance summaries. The objective of this research is to develop a digital attendance system that improves recording accuracy and simplifies attendance monitoring. The research method consists of requirement identification, system design, implementation, testing, and evaluation. The system is developed with features including user login, check-in and check-out recording, location tracking, attendance history, and automated monthly summaries. System testing is conducted to ensure proper functionality and usability. The results indicate that the system successfully records attendance data in a structured manner, provides time and location information, and automatically generates monthly reports. The novelty of this research lies in the integration of time tracking, location recording, and automated attendance reporting within a single system that enhances monitoring efficiency and effectiveness.